Towards right to work: A reflexive analysis on an action research - Sathyan, Arsha V (Action research (London, England), 2025)
This article explores the potential of action research by evaluating the research process, methodological nuances and experiential learnings of an action researcher involved in the action research conducted at Dudhera, a rural village in India on Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA). It documents the struggles and resistance of MGNREGA workers of Dudhera. They came together and decided to claim rights under MGNREGA when they felt powerless and starved - of both information and influence over the key decisions that affected their lives. The article critically examines the implementation failure of MGNREGA and the malpractices perpetuated by the Panchayat. It also portrays the community’s determination to bring change by claiming their right and challenging the status quo. The article also presents a reflexive analysis of action research, including the role of action researcher, community engagement and subjective transformation of both self and community in the action research process. The article advances knowledge about participatory action research and its potential for transformative change.